Accreditation Surveyor and Patient Safety: Learning from World Patient Safety Day 2023 (Literature Review) - Ahyar Wahyudi; Friedrich Max Rumintjap; Hisnindarsyah; Nurhikmah; Listyo Yuwanto (Formosa Journal of Science and Technology, 2023)
This article serves as a commemoration for World Patient Safety Day (WPSD) 2023, observed every 17th of September. Unlike previous years, this year’s theme is "Engaging Patients for Patient Safety" with the slogan "Elevate the voice of patients!". All parties are encouraged to actively participate and collaborate in involving patients and their families in their care. This involvement encompasses primary and secondary care facilities, whether in-patient or outpatient settings, community health clinics or hospitals. The role of surveyors has been further enhanced to evaluate and proactively ensure the participation of patients and their families in their care. Numerous studies have shown that the roles of surveyors, be it in guidance or accreditation, are crucial in ensuring this engagement occurs and that improvements in patient safety and quality are achieved. Accreditation surveyors play a vital role in supporting and developing patient safety practices that actively involve patients. They assist health facilities in understanding and adhering to required patient safety standards while facilitating collaboration between patients, families, and care teams. The role of surveyors in ensuring patient safety becomes increasingly relevant and essential in the pursuit of safer and higher-quality healthcare services.